2020
DOI: 10.1091/mbc.e19-11-0652
|View full text |Cite
|
Sign up to set email alerts
|

Coupling to substrate adhesions drives the maturation of muscle stress fibers into myofibrils within cardiomyocytes

Abstract: Focal adhesions have been known to be involved in the assembly of sarcomere-containing myofibrils for decades. Here, we define several molecular players required for the connection between adhesions and myofibrils and show that the strength of this connection positively correlates with myofibril maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
(105 reference statements)
0
21
0
Order By: Relevance
“…Here, we show that the architecture needed for active force transmission across the length and width of the cardiomyocyte is already formed at birth, as a singular myofibrillar network spanning the entire cross-sectional diameter of the cell can be seen in the P1 cardiomyocytes (electronic supplementary material, video S2). While our earliest timepoint here was P1, it is likely that myofibrillar networks form in the heart before birth as evidence of significant sarcomere branching can be found in both embryonic cardiomyocytes [60] and in human-induced pluripotent stem cell-derived cardiomyocytes [61]. Moreover, similar to skeletal muscle cells [3], the connectivity of cardiac contractile networks is dynamic throughout postnatal development (figure 1), with sarcomere branching most frequent at P7, then decreasing at P14 and again at P42.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that the architecture needed for active force transmission across the length and width of the cardiomyocyte is already formed at birth, as a singular myofibrillar network spanning the entire cross-sectional diameter of the cell can be seen in the P1 cardiomyocytes (electronic supplementary material, video S2). While our earliest timepoint here was P1, it is likely that myofibrillar networks form in the heart before birth as evidence of significant sarcomere branching can be found in both embryonic cardiomyocytes [60] and in human-induced pluripotent stem cell-derived cardiomyocytes [61]. Moreover, similar to skeletal muscle cells [3], the connectivity of cardiac contractile networks is dynamic throughout postnatal development (figure 1), with sarcomere branching most frequent at P7, then decreasing at P14 and again at P42.…”
Section: Discussionmentioning
confidence: 99%
“…Laser ablation is a widely used biophysical tool to assay the mechanical properties of cytoskeletal systems, such as stress fibers, epithelial cell–cell junctions and myofibrils (Fernandez‐Gonzalez, Simoes, Röper, Eaton, & Zallen, 2009; Lee et al, 2018; Roman et al, 2017; Taneja, Neininger, & Burnette, 2020). We have previously used this technique to interrogate cortex mechanics during cell division, as well as testing mechanical coupling between cell‐ECM adhesions and myofibrils (Taneja et al, 2020; Taneja, Neininger, & Burnette, 2020). Myofibrils are considered complex mechanical systems.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have implicated actin–titin interactions, collagen fibrils, and microtubule tyrosination as potential regulators of myofibril viscosity (Caporizzo et al, 2018; Granzier & Irving, 1995; Kulke et al, 2001). We have previously shown that FAK inhibition results in stabilization of cell‐ECM adhesions, which leads to increased incorporation of titin (Taneja, Neininger, & Burnette, 2020). Therefore, one possible mechanism could be due to increased actin–titin interactions mediated by increased cell‐ECM adhesion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations